Tungsten Bronze-Type Ceramics for Temperature-Stable Energy Storage Properties: A Feasibility Study - Shi, Xi; Khansur, Neamul Hayet (Crystals, 2023)
The temperature-dependent energy storage properties of four tungsten bronze-type ceramics are studied together with an investigation of their structure and temperature-dependent permittivity response, i.e., Ba6Ti2Nb8O30 (BTN), Ba6Zr2Nb8O30 (BZN), Sr3TiNb4O15 (STN) and Sr3ZrNb4O15 (SZN) ceramics. With different cations at A and B sites, those four ceramics exhibit different crystal structures and show significantly different microstructure features and dielectric responses with changing temperatures. It was observed under SEM that BZN has smaller grains and a more porous structure than BTN. SZN shows the most porous structure among all samples, exhibiting a much lower permittivity response than other samples with no signs of phase transitions from room temperature to 400 °C. Though the energy storage response of those samples is generally quite low, they exhibit good temperature stability together with low dielectric loss. It was suggested that by obtaining a denser structure through chemical modification or other methods, those tungsten bronze ceramics with good temperature stability could be promising as energy storage devices when improved energy storage properties are achieved.
CRIS-Team Scopus Importer:2023-08-11
Keywords: energy storage properties; porous ceramics; tungsten bronze-type ceramics